Volume 4B: Combustion, Fuels and Emissions 2014
DOI: 10.1115/gt2014-26742
|View full text |Cite
|
Sign up to set email alerts
|

Laminar and Turbulent Flame Speeds for Natural Gas/Hydrogen Blends

Abstract: Hydrogen-based fuels have become a primary interest in the gas turbine market. To better predict the reactivity of mixtures containing different levels of hydrogen, laminar and turbulent flame speed experiments have been conducted. The laminar flame speed measurements were performed for various methane and natural gas surrogate blends with significant amounts of hydrogen at elevated pressures (up to 5 atm) and temperatures (up to 450 K) using a heated, high-pressure, cylindrical, constant-volume vessel. The hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, in this study, the difference in the LBO limit due to the change in the heat load was not shown clearly because the change of the flame speed is large under low conditions [25] and we changed the condition at 0.02 intervals, which was a considerably large interval for observing differences in LBO limits. In addition, the fact that the flame speed increase caused by increase in Reynold number in high heat load conditions [26] was contributed to no distinct change of LBO limit with respect to increase of heat input.…”
Section: Resultsmentioning
confidence: 99%
“…However, in this study, the difference in the LBO limit due to the change in the heat load was not shown clearly because the change of the flame speed is large under low conditions [25] and we changed the condition at 0.02 intervals, which was a considerably large interval for observing differences in LBO limits. In addition, the fact that the flame speed increase caused by increase in Reynold number in high heat load conditions [26] was contributed to no distinct change of LBO limit with respect to increase of heat input.…”
Section: Resultsmentioning
confidence: 99%
“…The primary mechanism of laminar flame speed augmentation of straight-chain alkanes with hydrogen addition is predominantly a kinetic effect through increased concentration of the highly diffusive hydrogen radical [13]. A mechanistic and experimental study on the increased laminar speeds with hydrogen addition to NG2 and CH4 was conducted by the author's laboratory, and can be found elsewhere [14]. In that study, laminar flame speeds of methane/hydrogen and NG2/hydrogen mixtures were measured at elevated pressures and temperatures.…”
Section: Test Matrixmentioning
confidence: 99%
“…Hydrogen (H2) blending, sourced from various waste and sustainable processes, has also been proposed towards decarbonised gas networks. With the growing share of renewable energy sources, coupled with the demand of high-efficiency and low-emission power plants, combustor flexibility is of increasing importance in meeting the dynamic requirements of power generation systems, in terms of load and fuel variations [3]. Variations in natural gas composition and potential H2 enrichment presents significant combustion challenges to power generation gas turbines [4], particularly those running near the lean-limit, as this combustion regime tends to exacerbate any variation in flame behaviour, potentially leading to flame instability or extinction [5].…”
Section: Introductionmentioning
confidence: 99%
“…Such simplification is not problematic in the case of the quasi equi-diffusive lean CH4/air mixtures. However, issues potentially arise with increased concentrations of alternative fuels which has led to increased interest in this field [3,[10][11][12][13]. Recent DNS studies characterised the influence of Le for a range of pure and blended fuels (H2, CH4 and C3H8) demonstrating an amplification of the diffusive effects, according to each fuels' Le behaviour [8,10,12,14].…”
Section: Introductionmentioning
confidence: 99%